Reconfiguring radio drama after television: the historical significance of Theater 5, Earplay and CBS Radio Mystery Theater as post-network radio drama. Issue 4 (1st October 2016) - Patterson, Eleanor
Abstract : This article examines how the production of radio drama changed after the advent of television in the United States, specifically looking at the period between 1962 and 1982. Although there is a long-standing myth that radio drama died in the United States once television became the dominant source of domestic entertainment in the 1960s, ABC, NBC, CBS and Mutual radio networks all, at some point, had new radio drama programming in development in the 1960s and after. Furthermore, the introduction of formalized public radio policies, funding and structures in the late 1960s and early 1970s further opened up alternative spaces where radio drama was being made. This research demonstrates that the transition from radio entertainment to television entertainment by both sponsors and audiences in the United States was not predetermined, smooth, nor comprehensive. However, the production of radio drama became reconfigured amid the new post-network radio industry logics that favored narrowcasting, conceived of audiences as distracted listeners, and associated scripted radio with the outdated practices and technologies of the radio network era. This essay outlines key shifts in the production of radio drama after the ascension of television in the United Sates using ABC Radio's Theater 5 (1964–5), NPR's Earplay (1971–81) and CBS's Radio Mystery Theater (1974–82) as case studies.